A Review of Criminal Law on The Phenomenon of Teenage Illegal Sprint Racing during Ramadan - Isnawan, Fuadi (Universitas Serang Raya, 2024)
Illegal sprint racing is a prominent type of adolescent delinquency in Indonesia, especially during Ramadan. This occurrence not only undermines public order but also violates various applicable laws. This study employs a normative legal approach, with a focus on legal principles, to identify positive legal doctrines relevant to the phenomenon of illegal sprint racing. A case study approach is used to investigate various aspects of the phenomenon using primary legal texts such as the Law on Roads, the Law on Road Traffic and Transport, and the Law on Policing. The investigation found that illicit sprint racing without appropriate license is a severe violation of the law. The findings demonstrate the critical role that law enforcement plays in preserving community welfare, security, and order in locations that are frequently the scene of illicit sprint racing. Repressive law enforcement, more frequent patrols, and raising community understanding of the law are all effective ways to address this issue. The goal of socializing legal awareness is to increase community knowledge of relevant laws and regulations, and routine patrols are carried out to stop and identify illegal activity before it gets a chance to start. Repressive law enforcement makes it clear to offenders that their actions will not be accepted.